Penilaian Kinerja Manajemen melalui Analisis Laporan Keuangan - Ni Kadek Kori Pardiastuti; Nyoman Trisna Herawati (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
This research aims to determine the achievements achieved by the Company during the period 2018 and 2019, besides the purpose of this research is to know the efforts that the company has in increasing the company's profit. The subject of this study was the company's friend's in Bali CyclingTour. The object of this research is the assessment of performance management and analysis of financial statements. Methods of collecting data using documentation methods and interviews. This research uses quantitative descriptive data analysis. The results showed that the performance management of friend's in Bali CyclingTour was very well developed. Through the analysis of financial statements, the performance of company management is seen to increase assets in the form of vehicles and buildings. The company has several efforts to increase sales profit. The first effort is through online promotion, where the company works with online sites such as Airbnb and Get Your Guide. Secondly through offline promotion, where the company distribute brochures about the company to hotels in Bali.